2010
DOI: 10.1348/014466609x468042
|View full text |Cite
|
Sign up to set email alerts
|

Losing on all fronts: The effects of negative versus positive person‐based campaigns on implicit and explicit evaluations of political candidates

Abstract: The current research investigated the effects of negative as compared to positive person-based political campaigns on explicit and implicit evaluations of the involved candidates. Participants were presented with two political candidates and statements that one of them ostensibly said during the last political campaign. For half of the participants, the campaign included positive remarks about the source of the statement (positive campaign); for the remaining half, the campaign included negative remarks about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 63 publications
(124 reference statements)
4
55
1
4
Order By: Relevance
“…An IAT using pictures of the leaders of the right-and left-wing coalitions predicted vote choice one month prior to the election. Carraro, Gawronski, and Castelli (2010) and used various implicit measures to contribute new elements to the discussion on negative campaigning. For those who reported being undecided at a preelection interview regarding their potential vote, implicit attitudes predicted vote choice, even controlling for conscious attitudes expressed at the earlier interview.…”
Section: Political Psychological Extensions To Votingmentioning
confidence: 99%
“…An IAT using pictures of the leaders of the right-and left-wing coalitions predicted vote choice one month prior to the election. Carraro, Gawronski, and Castelli (2010) and used various implicit measures to contribute new elements to the discussion on negative campaigning. For those who reported being undecided at a preelection interview regarding their potential vote, implicit attitudes predicted vote choice, even controlling for conscious attitudes expressed at the earlier interview.…”
Section: Political Psychological Extensions To Votingmentioning
confidence: 99%
“…Using attack rhetoric illuminates and strengthens the 'cognitive footprint' of these ad messages because it increases their visibility and accessibility to become more memorable and comprehensible. Consequently the informative and motivating characteristics of attack messages engage the electorate, expanding voter turnout (Brader 2005 ;Carraro et al 2010 ;Finkel and Geer 1998 ;Geer and Geer 2003 ;Martin 2004 ). However, these cognitively engaging effects are statistically weak and require circumspection.…”
Section: The Persuasiveness Of Negative Attack Ad Messagesmentioning
confidence: 99%
“…Research on the positive effects of political advertising advances understanding in two areas: candidate evaluation and political motivation (Brader 2006 ;Carraro et al 2010 ;Matthews and Dietz-Uhler 1998 ;Westen 2007 ).…”
Section: The Infl Uence Of Positive Election Ad Messagesmentioning
confidence: 99%
“…For example, Carraro, Gawronski, and Castelli (2010) found that negative (versus positive) campaigning by one of the candidates leads to less favorable implicit attitudes towards both political candidates, whereas explicit attitudes only become less favorable for the candidate who negatively campaigned about his opponent. In other words, explicit attitudes toward the candidate who produced the negative information, but not the candidate being talked about negatively, became less favorable.…”
Section: Applications In Advertising Researchmentioning
confidence: 99%
“…The studies that found advertising to have a different impact on implicit than explicit attitudes (Carraro et al, 2010;Forehand & Perkins, 2005;Häfner & Trampe, 2009) can also be explained in terms of the different evaluative processes. In these studies, there were rather obvious cues that the intention of the advertisement was to persuade people (think about the celebrity voice-overs, the skinny models, and the negative campaigns of political candidates).…”
Section: What Attitude Dissociations Revealmentioning
confidence: 99%